Elementary Students Reading Engagement: the Impact of Story-Telling in EFL Reading Comprehension - Ida Yulianawati; *Kardi Nurhadi; Aresta Dian Mayasari (Universitas Syiah Kuala, 2022)
This study is aimed to report elementary students' engagement and perception of the use of storytelling in reading comprehension. The use of storytelling as one of the oldest ways of human communication is already known. It is also one of the pedagogical tools to develop language skills in first, second, and foreign languages regardless of students' age, gender, and ethnicity. Storytelling proved to be more effective in language teaching than traditional teaching material because it is fun, engaging, and raises students' interest in listening to the stories as well as retelling them. Meanwhile, reading is a crucial aspect of life, improving brain performance, increasing knowledge, and sharpening memory. This research employed a case study with a qualitative approach. The participants of the study were 31 elementary school students. The data were derived from classroom observations, questionnaires, and interviews. The results showed that the students engaged in the activity in storytelling class. The questionnaire and observational data indicated that the children responded positively to storytelling activity and engage the students to the reading class, motivating students' behavior and attitudes in EFL reading activity. Drawing on the findings, pedagogically, this study implied story telling can be adopted as the scaffolding to engage students in reading comprehension situated in elementary school context.